Sensorimotor processing for balance in spinocerebellar ataxia type 6. Issue 9 (16th April 2015) - Bunn, Lisa M.; Marsden, Jonathan F.; Voyce, Daniel C.; Giunti, Paola; Day, Brian L.
Abstract Background We investigated whether balance impairments caused by cerebellar disease are associated with specific sensorimotor processing deficits that generalize across all sensory modalities. Experiments focused on the putative cerebellar functions of scaling and coordinate transformation of balance responses evoked by stimulation of single sensory channels. Methods Vestibular, visual, and proprioceptive sensory channels were stimulated in isolation using galvanic vestibular stimulation, moving visual scenery, and muscle vibration, respectively, in 16 subjects with spinocerebellar ataxia type 6 (SCA6) and 16 matched healthy controls. Two polarities of each stimulus type evoked postural responses of similar form in the forward and backward directions. Disease severity was assessed using the Scale for Assessment and Rating of Ataxia. Results Impaired balance of SCA6 subjects during unperturbed stance was reflected in faster than normal body sway (P = 0.009), which correlated with disease severity (r = 0.705, P < 0.001). Sensory perturbations revealed a sensorimotor processing abnormality that was specific to response scaling for the visual channel. This manifested as visually evoked postural responses that were approximately three times larger than normal (backward, P < 0.001; forward P = 0.005) and correlated with disease severity (r = 0.543, P = 0.03). Response direction and habituation properties were no different from controls for all three sensory modalities. Conclusion Cerebellar degeneration disturbs the scaling of postural responses evoked by visual motion, possibly through disinhibition of extracerebellar visuomotor centers. The excessively high gain of the visuomotor channel without compensatory decreases in gains of other sensorimotor channels provides a potential mechanism for instability of the balance control system in cerebellar disease. © 2015 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.